Late nesting makes Barnacle Geese Branta leucopsis sensitive to anthropogenic disturbance in the Russian part of the Baltic Sea - Kouzov, Sergey A.; Zaynagutdinova, Elmira M.; Kravchuk, Anna V. (Wildfowl, 2019)
Barnacle Geese Branta leucopsis have bred in the Russian part of the Gulf of Finland since 1995. The species starting to breed in this area later than in the western Baltic Sea and North Sea regions, which were first colonised in the 1970s and early 1980s respectively. Since then, the breeding distribution has continued to expand through Lake Ladoga to Lake Onega in northwest Russia, which currently forms the north-easternmost limit of the range for of this temperate-breeding population. Nowadays, Barnacle Geese in the Russian part of the Gulf of Finland breed later than in other Baltic countries, including neighbouring Finland. The egg-laying period, which starts between 1 May–25 June and peaks during 11–25 May, is longer than for Barnacle Geese nesting in western parts of the temperate zone and also in comparison with those breeding in the Russian Arctic. The mean clutch size of 4.95 (s.e. ± 0.07) eggs is however larger than in other parts of the Baltic and in Arctic areas. Nests were found only on islands occupied by Herring Gulls Larus argentatus, which is the most common predator of Barnacle Goose eggs in the region. The Herring Gulls’ egg-laying period lasted from April to June; thus, incubation of Barnacle Goose eggs occurs during the gulls’ nesting and brood rearing period. It is suggested that anthropogenic disturbance could adversely affect Barnacle Goose breeding success in the Russian part of the Gulf of Finland, through tourist activity displacing geese from their nests at a time when the gulls are also breeding nearby. Specific features of the environment (late spring, predation risk and tourist activity) and the characteristics of this particular goose population (recent colonisation of the area, small population size and late breeding period) should be taken into account in developing conservation management programmes for geese in the region.